Pelatihan Sumberdaya Manusia (SDM) yang Berkualitas melalui Pengenalan Dasar-Dasar Akuntansi - Siarwi, Siarwi; Prastiani, Siti Chairunisa; Azzahra, Chairunnisa (Jurnal PKM Manajemen Bisnis, 2024)
Human Resources (HR) is a very important factor that cannot be separated from an organization, whether a company or an institution. Apart from that, HR is also a factor that influences the development of an organization. Efforts to increase human resource capacity at the Al - Farhan Darussalam orphanage Islamic boarding school/orphanage so that it is directed according to needs and dynamics. Accounting is a part of economics that has an important role for companies. The aim of this Community Service is to improve the quality of natural resources through basic accounting training for Darussalam Foundation youth. The method used in this activity is the extension method. through lecture methods, discussions and questions and answers. This activity resulted in increased knowledge for Darussalam Foundation teenagers regarding basic accounting.